(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Thisstudy explores the concept of media ethics with special reference to the Indiannews media. In India media ethics have been a convention associated with thetraditional mass media. But with the development in technology and the adventof the internet the standard ethical practices are facing continuous challenge.This paper discusses three incidents where the traditional mass media - thepress or television - deviated from the established ethical principles andjournalistic norms normally practiced by the Indian news media. This paper willexplore those aberrations and analyze the ethical principles of the news mediathat has been manipulated for a more worldly purpose. The paper drawsconclusion on the future of media ethics in the context of Indian news media.